Pengaruh Sistem Informasi Audit Pegeluaran Waste Menjadi Kain Menggunakan Web Bekerjasama Negara Jerman di PT. Hasil Damai Textile Bandung - Cahyadi Agustin (INFOKOM (Informatika & Komputer), 2020)
This study aims to design a waste disposal information system processed into cloth in collaboration with the German state and web-based using the php mysql database at PT. Hasil Damai Textile. The software development method using a waterfall from the research conducted, found that the problem that occurs is the recording process using Microsoft Excel so that it takes a relatively long time and the results of calculations are inaccurate, as well as unsafe and irregular data storage. making it difficult to identify trash.